Clinical encounters of Australian general practice registrars with Aboriginal and Torres Strait Islander patients. (10th August 2015) - Thomson, Allison; Morgan, Simon; O'Mara, Peter; Tapley, Amanda; Henderson, Kim; van Driel, Mieke; Oldmeadow, Christopher; Ball, Jean; Scott, John; Spike, Neil; McArthur, Lawrie; Magin, Parker
Abstract: Objective: General practice is central to Aboriginal and Torres Strait Islander health care, and this area is a core element of Australian general practice (GP) training. We aimed to describe the prevalence, nature and associations of GP registrar encounters with Aboriginal and Torres Strait Islander patients. Methods: A cross‐sectional analysis from a cohort study of GP registrars' clinical consultations 2010–2013. Registrars record demographic, clinical and educational details of consecutive patient encounters. Multivariable associations were tested with logistic regression. Results: A total of 592 registrars contributed data from 69, 188 consultations. Encounters with Aboriginal and Torres Strait Islander patients comprised 1.0% of consultations. Significant positive associations included younger patient age; new patient to the registrar; lower socioeconomic status of practice location; non‐urban practice setting; more problems managed; and follow‐up arranged. A greater proportion of Aboriginal and Torres Strait Islander patients' problems were psychological/social and a lesser proportion were cardiovascular. Consultation duration did not differ between the two groups Conclusions: GP registrars encounter Aboriginal and Torres Strait Islander patients less than do established GPs. Our results suggest possible variability in registrar experience of Aboriginal and Torres Strait Islander health. Implications: Our findings will inform training of a culturally and clinically competent workforce in this area.